Transition voltage of AlGaN/GaN heterostructure MSM varactor with two-dimensional electron gas. (November 2017) - Osvald, J.; Vanko, G.; Chow, L.; Chen, N.C.; Chang, L.B.
Abstract: It is not in principle clear which of the capacitors forming a varactor is responsible for the capacitance change at the transition voltage. We analyzed a theoretical case of transition voltage of the varactor formed by ideal Schottky diodes. Since real devices often do not behave strictly according to thermionic theory we also analyzed the transition voltage of experimental metal-semiconductor-metal (MSM) varactor with a two-dimensional electron gas and an MSM varactor with a dielectric layer. We found that the transition voltage of the MSM varactor was determined by the reverse-biased diode of the varactor. A voltage drop on the forward-biased diode was too low to spill over electrons in the AlGaN layer and to reduce the capacitance of the structure. The transition voltage of the MSM varactor was therefore very close to – the threshold voltage of the single diode. The situation was different with the MSM varactor with higher leakage current or in MSM varactor with the dielectric layer. The voltage drop on the forward-biased diode is no more negligible and both parts of the varactor were polarized by voltage drops on them that were caused by direct current flow. In this case, the transition voltage of the varactor was enhanced by the voltage drop on the forward-biased diode. Since the transition voltage determines the voltage region in which the varactor protect circuit devices connected in series to the varactor the presented results may help to tune this voltage region. Highlights: The transition voltage of the MSM varactor was studied theoretically and experimentally. The transition voltage of MSM varactor with Schottky diode is almost the same as the threshold voltage of the single diode. The transition voltage is determined by the reverse polarized diode. For MSM varactor with a dielectric layer the transition voltage increases by voltage drop on the forwardly polarized diode.